Interaction of FACTS devices with loads dynamics in the transport networks and interconnection - Kamal Mohammed Saleh Al-Azzawi; Muntadher Ali Abd (Institute of Advanced Engineering and Science, 2022)
This paper introduced analysis and improvement of power networks stability. It focused on the impact of flexible AC transmission systems (FACTS) device interaction with the other components of the network. It investigated the impact of dynamic charges on the ability of FACTS to eliminate power oscillations problems. A small-signal analysis, frequency analysis and non-linear time simulations using EUROSTAG made it possible to study these problems. Other, research has shown that the damping loops of the power oscillations effects using classical techniques of sensibility are not robust in relation to the variations of load models. Thus, this paper proposed a method based on the sensitivity of the eigenvalues and it takes into account the variations of the load models. The method calculates an optimal phase compensator based on a weighted average of the sensitivity of the target mode. It considers the variations of sensitivity as a function of the uncertainty in the load model. According to the obtained results, this method is effective in most stability problems.